Respostas
respondido por:
1
a) 9x -3= 5x
9x -5x = 3
4x = 3
x= 3/4
b) 5(x +2) -3(x +6) = 40
5x +10 -3x -18= 40
2x= 40 -10 +18
2x = 48
x= 48/2
x= 24
c)17 +50= 7x
67= 7x
x= 67/7...fica assim em forma de fração
d) 7(2 +x) = 35 + ( x-2)
14 +7x = 35 +x -2
7x -x = -2 +35 -14
6x = 19
x= 19/6...fica em forma de fração
Espero ter ajudado!!
9x -5x = 3
4x = 3
x= 3/4
b) 5(x +2) -3(x +6) = 40
5x +10 -3x -18= 40
2x= 40 -10 +18
2x = 48
x= 48/2
x= 24
c)17 +50= 7x
67= 7x
x= 67/7...fica assim em forma de fração
d) 7(2 +x) = 35 + ( x-2)
14 +7x = 35 +x -2
7x -x = -2 +35 -14
6x = 19
x= 19/6...fica em forma de fração
Espero ter ajudado!!
tatahZn:
na letra A fica em forma de fraçao???
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás